High-intensity focused ultrasound ablation by the dual-frequency excitation - Law, Berlinda Siu Kwun (2021)
High-intensity focused ultrasound (HIFU) has emerged as an effective and noninvasive therapeutic modality for cancer and solid tumor. Despite its promising clinical outcomes and the approval of the Food and Drug Administration of many countries, the ablation time of a large target is long, so enhancement of the lesion production is highly desired. In this study, dual-frequency (or amplitude modulation) excitation was evaluated both numerically and experimentally, and its performance was compared with that using single-frequency excitation at the same power output. The nonlinear wave propagation model was used to simulate the acoustic field of HIFU exposure, the Gilmore model was used to determine the induced bubble dynamics, and then absorbed acoustic energy and bubble-enhanced heating were put into the BioHeat equation to calculate the temperature elevation. HIFU-produced lesion in the bovine serum albumin-embedded polyacrylamide was recorded photographically. It is found that dual-frequency excitation (3.16 + 3.20MHz) can increase the lesion area by 35%-65% compared to single-frequency excitation (3.18 MHz) at the same power output. The lesion enhancement increases with the pulse repetition frequency, duty cycle, and modulation depth and decreases with the frequency difference. In summary, dual-frequency excitation can increase the bubble cavitation and the associated heating for HIFU ablation for large lesion production.